2008
DOI: 10.1093/eurheartj/ehp005
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion ventricular arrhythmia 'bursts' predict larger infarct size despite TIMI 3 flow restoration with primary angioplasty for anterior ST-elevation myocardial infarction

Abstract: Aims Successful epicardial reperfusion with primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) can paradoxically evoke myocardial reperfusion injury, which may be signalled by temporally associated ventricular arrhythmias (VAs). We correlated reperfusion VA 'bursts' with final infarct size (IS) in patients with restored TIMI 3 flow following PCI for anterior STEMI. Methods and results All 128 anterior STEMI patients with final TIMI 3 flow had continuous 24 h digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 32 publications
4
46
0
1
Order By: Relevance
“…It is well accepted in the literature that I/R induces cellular damage that makes the myocardium more susceptible to arrhythmogenesis, and thus reperfusion-induced arrhythmias are considered as indicators of I/R injury (Engelen et al, 2003;Majidi et al, 2009). For instance, Majidi et al reported that the presence of reperfusion arrhythmia bursts in STEMI patients is associated with a worse outcome (larger infarct size and decreased ejection fraction) (Majidi et al, 2009). However, here we found surprisingly that longer than 60 s reperfusion-induced VT/VF was associated with a decreased infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted in the literature that I/R induces cellular damage that makes the myocardium more susceptible to arrhythmogenesis, and thus reperfusion-induced arrhythmias are considered as indicators of I/R injury (Engelen et al, 2003;Majidi et al, 2009). For instance, Majidi et al reported that the presence of reperfusion arrhythmia bursts in STEMI patients is associated with a worse outcome (larger infarct size and decreased ejection fraction) (Majidi et al, 2009). However, here we found surprisingly that longer than 60 s reperfusion-induced VT/VF was associated with a decreased infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…After the last medication, the SD rats were anesthetized with sodium pentobarbital (1.2 mg/kg) and the heart with a section of the aorta was removed from the chest. The heart was then reversely perfused through the aorta with a modified Langendorff perfusion system using oxygenated Krebs-Henseleit (K-H) buffer containing (in mM): NaCl 118, NaHCO 3 25, D-glucose11, KCl 4.7, KH 2 PO 4 1.2, MgSO 4 1.17, and CaCl 2 2.5; pH 7.4. After perfusion for 10 minutes and cardiac parameters became stable, the heart was subjected to hypoxia by terminating perfusion with the oxygenated K-H buffer.…”
Section: Animalsmentioning
confidence: 99%
“…However, reperfusion of ischemic myocardium is often associated with further myocardial damage, which is recognized as myocardial ischemia-reperfusion (I/R) injury [1,2]. In addition to inducing myocardial ischemia and hypoxia, myocardial I/R injury alters excitability and conduction system of cardiac muscles, impairs cardiac diastolic and systolic function, and triggers severe myocardial injury and dysfunction, such as cardiac arrhythmias, myocardial energy metabolism failure, myocardial stunning and microvascular dysfunction [3,4]. Therefore, protection of the heart from myocardial I/R injury with an aim to improve patient's clinical outcomes is a key research implication in the field of cardiovascular protection.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with thrombolytic therapy, reperfusion VAs were considered a positive event as a non-invasive marker of infarct artery recanalization [2]. In the more contemporary era of direct percutaneous coronary intervention (PCI), where TIMI 3 epicardial flow is restored in N 90% of STEMIs and mortality has been reduced to less than 5% [3], the hypothesis that VA "bursts" are associated with larger infarct size (IS) and worsened outcomes in the setting of anterior MI has been proposed by our group, based on retrospective modeling [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%